Necroptotic kinases are involved in the reduction of depression-induced astrocytes and fluoxetine’s inhibitory effects on necroptotic kinases - Zeb, Salman; Ye, Huan; Liu, Yuan; Du, Hua-Ping; Guo, Yi; Zhu, Yong-Ming; Ni, Yong; Zhang, Hui-Ling; Xu, Yuan (Frontiers in Pharmacology, 2023)
The role of astrocytes in major depressive disorder (MDD) has received great attention. Increasing evidence indicates that decreased astrocyte numbers in the hippocampus may be associated with depression, but the role of necroptosis in depression is unknown. Here, in a chronic unpredictable mild stress (CUMS) mouse model and a corticosterone (Cort)-induced human astrocyte injury model in vitro, we found that mice treated with CUMS for 3 weeks to 5 weeks presented depressive-like behaviors and body weight loss, accompanied by a reduction in astrocytes and a decrease in astrocytic BDNF, by activation of necroptotic kinases, including RIP1K (receptor-interacting protein 1 kinase)/p-RIP1K, RIP3K (receptor-interacting protein 3 kinase)/p-RIP3K and MLKL (mixed lineage kinase domain-like protein)/p-MLKL, and by upregulation of inflammatory cytokines in astrocytes of the mouse hippocampus. In contrast, necroptotic kinase inhibitors suppressed Cort-induced necroptotic kinase activation, reduced astrocytes, astrocytic necroptosis and dysfunction, and decreased Cort-mediated inflammatory cytokines in astrocytes. Treatment with fluoxetine (FLX) for 5 weeks improved CUMS-induced mouse depressive-like behaviors; simultaneously, FLX inhibited depression-induced necroptotic kinase activation, reversed the reduction in astrocytes and astrocytic necroptosis and dysfunction, decreased inflammatory cytokines and upregulated BDNF and 5-HT1A levels. Furthermore, FLX had no direct inhibitory effect on RIP1K phosphorylation. The combined administration of FLX and necroptotic kinase inhibitors further reduced Cort-induced astrocyte injury. In conclusion, the reduction in astrocytes caused by depression may be associated with the activation of necroptotic kinases and astrocytic necroptosis, and FLX exerts an antidepressive effect by indirectly inhibiting RIP1K-mediated astrocytic necroptosis.